2009
DOI: 10.1111/j.1582-4934.2008.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial nutrients improve immune dysfunction in the type 2 diabetic Goto‐Kakizaki rats

Abstract: The development of type 2 diabetes is accompanied by decreased immune function and the mechanisms are unclear. We hypothesize that oxidative damage and mitochondrial dysfunction may play an important role in the immune dysfunction in diabetes. In the present study, we investigated this hypothesis in diabetic Goto-Kakizaki rats by treatment with a combination of four mitochondrial-targeting nutrients, namely, R-α-lipoic acid, acetyl-L-carnitine, nicotinamide and biotin. We first studied the effects of the combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 49 publications
5
46
0
3
Order By: Relevance
“…The protective role of L-carnitine could also be attributed to its antioxidant role as observed by us and others (Rani and Panneerselvam 2002;Gulcin 2006) and thereby this could have contributed to its protective role on DNA. This is also supported by recent studies by Hao et al (2008) where in they observed 12 week long treatment of diabetic rats with a combination of mitochondrial targeting nutrients like L-carnitine enhanced immune functions, inhibited oxidative damage and apoptosis process.…”
Section: Discussionsupporting
confidence: 78%
“…The protective role of L-carnitine could also be attributed to its antioxidant role as observed by us and others (Rani and Panneerselvam 2002;Gulcin 2006) and thereby this could have contributed to its protective role on DNA. This is also supported by recent studies by Hao et al (2008) where in they observed 12 week long treatment of diabetic rats with a combination of mitochondrial targeting nutrients like L-carnitine enhanced immune functions, inhibited oxidative damage and apoptosis process.…”
Section: Discussionsupporting
confidence: 78%
“…These treatments also produced a non-significant decrease in p53 and p21 (Fig. 5), consonant with the statistically significant reduction in these two proteins seen in GK rat thymocytes reported earlier (15) . As evidence indicating a possible increase in oxidative stress and consequent cell death/tissue damage in GK rat mitochondria, amounts of oxidised proteins were clearly elevated in GK rats, and total antioxidant capacity, total superoxide dismutase, glutathione S-transferase and NAD(P)H:quinone oxidoreductase 1 activities were substantially decreased.…”
Section: Discussionsupporting
confidence: 69%
“…It is thus an appropriate model to study events occurring at the onset of diabetes, compared with obese diabetic rats which present severe hyperglycaemia and hyperlipidaemia (13) . Treatment of GK rats with mitochondrial nutrients significantly improves glucose tolerance, insulin release, plasma NEFA levels, skeletal muscle mitochondrial biogenesis (14) and immune function (15) . The rationale for the selection and dosage levels of these nutrients, as detailed earlier (14,15) , targets substances that influence mitochondrial processes either synergistically or by mechanisms as widely disparate as possible.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We attempted to cryopreserve isolated chick islets following an established protocol used for cryopreservation of mouse islets [57]. The islets were cryopreserved in a medium consisting of DMEM:Ham's F.12 (1:1) (Gibco, Brazil), supplemented with 10% FCS, riboflavin, and nicotinamide as cryoprotectants [58][59][60][61][62][63][64]. We found that it is possible to cryopreserve chick islets without losing viability and insulin secretory activity [13].…”
Section: Usability Of Chick Pancreatic Islets To Screen For Insulin Smentioning
confidence: 99%